Activación cerebral asociada a una tarea de lectura de sustantivos. - Trejo-Martínez, David; Marcos-Ortega, José; Ansaldo, Ana Inés; Armony, Jorge; Conde, Rubén; Velasco, Ana Luisa; Jiménez, Fiacro; Harmony, Talía (Revista Medica del IMSS)
Background: word reading involves several steps, from the visual perception of each of its constituting elements to its recognition as an entity with a specific meaning. Various brain structures participate in these processes, depending of the linguistic and cognitive characteristics of the stimulus. Our objective was to characterize brain activity through the use of functional magnetic resonance imaging (FMRI) associated with the process of nouns reading. Methods: eleven healthy right-handed volunteers participated in a lexical decision task involving 58 written nouns. An equal number of letter sequences were used as control stimuli. Reaction times were also recorded. Results: there was a difference (p < 0.05) in reaction time between nouns and letter sequences in the lexical decision task. FMRI contrasted between conditions revealed significant activations in several areas involved in reading. Conclusions: the brain activation may reflect the different perceptual demands associated with the initial processing of nouns, as compared to meaningless letter sequences. We attribute the difference between our results and those previously reported to the particular characteristics of the pronunciation rules of written Spanish.